2013
DOI: 10.1371/journal.pone.0070604
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and Let-7a micro-RNA Regulate K-Ras Activity in HCT116 Colorectal Cancer Cells

Abstract: Recent reports have indicated that KRAS and TP53 mutations predict response to therapy in colorectal cancer. However, little is known about the relationship between these two common genetic alterations. Micro-RNAs (miRNAs), a class of noncoding RNA implicated in cellular processes, have been increasingly linked to KRAS and TP53. We hypothesized that lethal-7a (let-7a) miRNA regulates KRAS through TP53. To investigate the relationship between KRAS, TP53, and let-7a, we used HCT116 KRASmut human colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…Previous studies have revealed that several miRNAs are involved in the regulation of KRAS gene expression in colorectal cancers (14,15). A preliminary microarray analysis of Caco-2 cell miRNAs following treatment with 2.5% coffee extract indicated that coffee induced expression of miR-30c and miR-96, which are known to target the KRAS gene (data not shown).…”
Section: Coffee Induced Mirnas That Target Kras Gene Expressionmentioning
confidence: 85%
“…Previous studies have revealed that several miRNAs are involved in the regulation of KRAS gene expression in colorectal cancers (14,15). A preliminary microarray analysis of Caco-2 cell miRNAs following treatment with 2.5% coffee extract indicated that coffee induced expression of miR-30c and miR-96, which are known to target the KRAS gene (data not shown).…”
Section: Coffee Induced Mirnas That Target Kras Gene Expressionmentioning
confidence: 85%
“…Known as a tumor suppressor miRNA, Let‐7a has been found to inhibit the growth of several tumor types, including osteosarcoma cells and breast cancer cells (54, 55); thus, our observation of increased cell proliferation in the flown cells was consistent with the down‐regulation of Let‐7a. Although the involvement of Let‐7a in changes in gravity has not been reported previously, it has been reported that radiation exposure and other stress factors induce changes in the Let‐7 family, and such changes are p53 dependent (56). Down‐regulation of Let‐7a has been reported in fibroblast cells (AG1522) used in the present study after exposure to g ray and UV ray radiation (57); however, it is unclear whether exposure to space radiation caused the change in Let‐7a expression in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Both TP53 and APC are tumour suppressor genes. A TP53 inhibits activated RAS through lethal (Let) 7a 23 . In the presence of TP53 mutation, Let-7a is not able to regulate activated RAS.…”
Section: Response To Preoperative Chemotherapymentioning
confidence: 99%